Kinerja Produksi Udang Vaname (Litopenaeus Vannamei) Yang Dipelihara Pada Sistem Intensif Dengan Kepatadan Berbeda - Toto Hardianto; Yunarty Yunarty; Siti Aisyah Saridu; Diana Putri Renitasari; Ardana Kurniaji; Andika Ramadani; Fanggi Fanggi (Universitas Mataram, 2024)
Vannamei shrimp (Litopenaeus vannamei) is a significant aquaculture commodity experiencing rapid global growth, including in Indonesia, to address the decline in production of tiger shrimp. This study aims to evaluate the impact of stocking density on vannamei shrimp production in an intensive aquaculture system. Conducted over four months at PT. Laut Biru Lombok’s intensive pond, the research compared two stocking densities (211 and 189 shrimp/m²) and assessed parameters such as growth, survival rate, feed conversion ratio, and productivity. Results indicated that a lower stocking density (189 shrimp/m²) generally provided better growth, survival, and feed conversion ratio, though productivity differences were not significant. In conclusion, a lower stocking density enhances the performance of vannamei shrimp in intensive aquaculture systems